Optimal maintenance service outsourcing strategy considering extended warranty service. (28th October 2022) - Cao, Kaiying; Su, Yunyi; Han, Guoxin; Wang, Jia
Abstract: In recent years, extended warranty (EW) services are widely provided by brand firms. Given that third‐party maintenance service providers have more maintenance cost advantages than brand firms, brand firms face the challenge of whether to enter the maintenance service market. To address the above challenge and issue, we develop theoretical models. The research shows that the cost coefficient of developing maintenance service plays a critical role in the optimal maintenance service operation strategy. And the base market sizes of the EW and the charged maintenance service have significant influences on the results. Moreover, we propose conditions for a win–win outcome.